(3LjhHhdJjcjG GdEQgGH aj GdTQb GdGhSW hGSJQGJjLjG GdehGLgIs - (3YeQ cGed(B, (3MSfs ((3YeGf(B:s (3OGQ GdNdjL ddfTQ hGdJhRjY(B,s, 2023)
(3ETcGdjGJ JMOjO eaghe GdEQgGH hLOdjI YdGbJg H(B((3GdLgGO(B)(3, ETcGdjGJ JMOjO eaghe GdEQgGH, GdGJLGgGJ GdfXQjI dJYQja GdEQgGH, LOdjI GdYdGbI Hjf GdEQgGH hGdLgGO, Ljh(B-(3JCQjNjI GdXGgQI GdEQgGHjI GdYGHQI ddMOhO hGJLGgGJ OQGSJgG, Ljh(B-(3JCQjNjI GdXGgQI GdEQgGHjI GdYGHQI ddMOhO, GdGJLGgGJ GdfXQjI dOQGSI GdXGgQI GdEQgGHjI, GdEQgGH YfGUQg hCTcGdg heYGjjQg heSHHGJg hCgOGag, YfGUQ hGTeGd heYGjjQ GdGQgGH, GdETeGdjGJ GdeSHHI ddEQgGH, CgOGa GdEQgGH, GdNQjWI GdchfjI dbhi GdEQgGH GdYGHQI ddMOhO, GdaGYdjf GdYfjajf ef GdOhd, GdaGYdjf GdYfjajf ef ZjQ GdOhd, JMdjd XGgQI GdEQgGH GdYGHQ ddMOhO hJCKjQg Ydi efWbI GdTQb GdChSW, LZQGajG GdYfa hGdJWQa aj GdTQb GdChSW, GdeJZjQGJ GdLjhSjGSjI hCKQgG aj JfGej XGgQI GdEQgGH GdYGHQ ddMOhO aj GdTQb GdChSW, GSJQGJjLjGJ GdJMQc GdLjhSjGSj hGdLjhYScQj dbhi GdEQgGH GdYGHQI ddMOhO aj GdTQb GdChSW, GdBKGQ GdLjhHhdjJjcjI d` (B((3GSJQGJjLjGJ(B) (3GdJfXjeGJ GdEQgGHjI Ydi GSJbQGQ hCef GdTQb GdChSW, GdEQgGH GdYGHQ ddMOhO hJCKjQGJg Ydi GdCef Gdbhej GdeUQj, LjhJGQjNjI GdXGgQI GdEQgGHjI hJeKdGJgG aj eUQ, OhGFQ GdJgOjO GdLjhHhdhJjcj ddJfXjeGJ GdEQgGHjI Ydi GdCef Gdbhej GdeUQj, OhGaY (B( (3eSHHGJ(B) (3GdXGgQI GdEQgGHjI aj eUQ, GdBKGQ GdLjhHhdJjcjI ddXGgQI GdEQgGHjI GdYGHQI ddMOhO Ydi eSJbHd OhdI eUQ, eSJbHd GdXGgQI GdEQgGHjIGdYGHQI ddMOhO aj OhdI eUQ, GdJfejI cGSJQGJjLjI dehGLgI GdEQgGH(B. s
(3eQGLY U(B.223s
Keywords: (3GdEQgGHs; (3GdLQGFe GdSjGSjI s; (3GdTQb GdChSWs; (3GdYfas